2020
DOI: 10.7861/fhj.2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the working experience of doctors in training

Abstract: Using an online tool, we report the association between tasks and 'affect' (underlying experience of feeling, emotion or mood) among 565 doctors in training, how positive and negative emotional intensity are associated with time of day, the extent to which positive affect is associated with breaks, and consideration about leaving the profession. Respondents spent approximately 25% of their day on paperwork or clinical work that did not involve patients, resulting in more negative emotions. Positive emotions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Similarly, Shah et al noted variation in timely hip fracture surgery with day, evening and night effects, suggesting similar multifactorial after-effects to those found here 29. Other recent studies have looked at the impact of daily scheduled tasks such as breaks, staff meetings and clinical tasks on staff stress and burnout 30. Despite this, our previous paper found no significant variation in care quality across 42 time periods in any of the measures relating to brain scanning, stroke nursing care and thrombolysis 13…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Similarly, Shah et al noted variation in timely hip fracture surgery with day, evening and night effects, suggesting similar multifactorial after-effects to those found here 29. Other recent studies have looked at the impact of daily scheduled tasks such as breaks, staff meetings and clinical tasks on staff stress and burnout 30. Despite this, our previous paper found no significant variation in care quality across 42 time periods in any of the measures relating to brain scanning, stroke nursing care and thrombolysis 13…”
Section: Discussionsupporting
confidence: 58%
“…29 Other recent studies have looked at the impact of daily scheduled tasks such as breaks, staff meetings and clinical tasks on staff stress and burnout. 30 Despite this, our previous paper found no significant variation in care quality across 42 time periods in any of the measures relating to brain scanning, stroke nursing care and thrombolysis. 13 Our findings revealed contrasting stakeholder views about the acceptability and quality of care at weekends Original research and at night.…”
Section: Comparison With Previous Literaturementioning
confidence: 77%
“…Complementing this passive data mining, and standing for active interventions, Lachish and co. found out, that continuous institutional support has a signi cant positive effect on safeguarding and long-term retention of junior physicians (13,14). Several earlier publications highlight the importance of questionnaires in understanding the experiences and views of physicians during training, which may ultimately make improvements in their working conditions and overall well-being (15)(16)(17). Integration of the above perspectives shed light on the need for continuous interns' satisfaction measurement using questionnaires, accompanied by supporting the cadets by continuous positive appraisal.…”
Section: Burnout Of Medical Professionals Begin Early In Careermentioning
confidence: 99%
“…As study design and break types under investigation varied markedly, they are described here by topic and data type to aid clarity, including quantitative studies of standard 30 min breaks, 24 25 sleep-related interventions (naps), 26 27 yoga and mindfulness interventions, [28][29][30][31] microbreaks in surgery, [32][33][34][35] other microbreak interventions, 36 37 surveys [38][39][40][41][42][43][44] and cohort studies. [45][46][47][48] Qualitative data are grouped into qualitative evaluations of interventions 49 50 and other qualitative studies, [51][52][53][54] and a single German sequential mixed-method study investigating the impact of breaks on opportunities for physicians to share (or hide) ignorance 55 (see online supplemental table 4).…”
Section: Impact Of Breaks On Well-being and Performance Outcome Measuresmentioning
confidence: 99%
“…One prospective cohort study in Belgium ED physicians 45 found that greater use of fatigue reduction strategies (break activities) were associated with faster reaction times but not with levels of burnout. A UK study in trainees 46 found that the lack of breaks during shifts was associated with greater negative affect (worry, tiredness, impatience, frustration, etc) and less positive affect (competence, enjoyment, happiness, etc). A retrospective cohort study using secondary analysis of electronic records in the US 47 found that doctors were more likely to inappropriately prescribe opioids before than after a break, while another in Switzerland 48 showed that report errors (as a surrogate marker of fatigue) reduced after breaks, though this postbreak effect waned as the week progressed.…”
Section: Quantitative Study Findings: Break Interventionsmentioning
confidence: 99%